Peningkatan aktivitas dan hasil belajar peserta didik pada pembelajaran IPA dengan penerapan pembelajaran kooperatif tipe bermain jawaban kelas V SDN 29 Siguntur Muda Kecamatan Koto XI Tarusan - Maidarly Maidarly (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
This research is motivated by activity and result of study IPA, especially biology which still low. Of the 23 students of class V, only nine complete learners and 29 students are not complete in achieving Minimum Exhaustiveness Criteria (KKM) on science learning in SDN. 29 Siguntur Muda Koto XI Tarusan. This is because students are less like learning science. This research is a Classroom Action Research (PTK) using the cooperative learning model type play answer. In this, studies are class V learners who numbered 23 students. Based on data analysis, it can be concluded that the use of cooperative learning model type of play answers can improve the activity and learning outcomes of science student's class V SDN. 29 Siguntur Muda Koto XI Tarusan.